Validity of Sports Competition Anxiety Tests for Amateur Boxing Athletes - Trisnar Adi Prabowo; Tomoliyus Tomoliyus; Fauzi Fauzi (Universitas PGRI Palembang, 2023)
Anxiety is a normal symptom that arises in athletes before the game, one of the sports that affects anxiety is boxing. The purpose of the study was to develop a sports competition anxiety test for amateur boxing athletes. This research method uses a mixed method by combining quantitative and qualitative approaches to collect valid and complete data. The participants of the study were 20 experts. The experts have a qualification of 3 expert lecturers in sports psychology, 7 national certified boxing coaches and have a master of sport science diploma, and 10 national certified boxing coaches. This validity test uses the Aiken' V formula with the delphi technique. In judging, experts are given assessment sheets as well as using scale values that include some specific values, the value of the scale is: value 1 = not appropriate, value 2 = less appropriate, value 3 = appropriate, value 4 = very appropriate. From these results, the sports competition anxiety test for boxing from the aspect of (1) the definition aspect of the sports competition anxiety test with instrument conformity has a coefisisen value of V of 0.950; (2) the material clarity aspect of anxiety with instrument conformity has a coefisisen value of V of 0.783; (3) the aspect of conformity of the statement to the conditions of the amateur boxing competition with the conformity of the instrument has a coefisisen value of 0.750; (4) the aspect of the suitability of the score with the anxiety category with the conformity of the instrument has a coefisisen value of V of 0.767; and (5) the procedure aspect of filling the test with instrument conformity has a coefisisen value of V of 0.900. Hence the anxiety test of sports competitions for amateur boxing is declared valid.